TRANSFORMASI TENAGA KERJAWANITA DARI SEKTOR PERTANIAN KE SEKTOR INDUSTRI DI KABUPATEN MOJOKERTO - Selamet Joko Utomo (MediaTrend, 2014)
Decreasing the percentage of the number of working population in the primarysector is a transformation of the economic development which originally dominated bythe agricultural sector to industry. The employment growth in the outside ofagricultural sector had expressed as one of the caracteristic of rural employmen. Thisresearch used logistic regression. The result of this research show that the low of thewages rate in agriculture sector is the primary reason for woman labor to move onindustry sector. The calculation results with logistic regression show that value ofeducation coefficient is 3,899. It means that probability for shift of woman labor withhigh school levelhad showed by possitive coefficient slope of education variable.Woman labor with senior high school graduate have higher shift oppotunity than woman labor with junior high school graduate. It can be looket by value of exp (B) at 49,356 times.